Formation of the Student Board at the UAE Centre for Academic Integrity - Our Initiatives and Experience - John, Serene Regi; Ramdas, Sruthi; Khan, Sara; Wilson, Sarah; Shabbir, Rukaiya (Canadian Perspectives on Academic Integrity, 2021)
The CAIU constitutes academicians, students, professionals and universities from UAE, working in collaboration with each other to promote and raise awareness about academic integrity. The CAIU was officially launched in the year 2020. How it all started? The idea to establish an Academic Integrity Centre in the UAE began in 2016, when the first International Conference on Academic Integrity was held in UAE at the University of Wollongong. The late professor Tracey Bretag and Dr. Teddi Fishman, were important pioneers in the process of building the centre. Since then, several efforts have been taken to collaborate and bring together the local universities and academicians under one roof for the benefit of the greater community. This ultimately led to the formation of the CAIU About the Centre The Vision of the Centre is “To bring together educators, students and industry to discuss, create and promote the culture of integrity across school and university campuses in the UAE.” The centre’s logo is depicted as the ‘Tree of Hope’. The tree in the logo represents the stage we have reached in launching the centre. The CAIU constitutes 2 leading committees - the Founding Board Members (FBM) and the Student Board. The FBM consists of 7 teachers and researchers who are at the forefront of leading the centre to achieving its goals and objectives. The Student Board consists of students from the local schools and universities. They closely interact and work with the FBM to organize and conduct various events across schools and universities in the UAE. Student Board Students play an important role in helping build a culture of academic Integrity and are the primary initiators for any activity, campaign or dialogue. The Center for Academic Integrity seeks out passionate students with strong voices and minds willing to volunteer their efforts to further its initiatives. With that purpose in mind, CAIU sent out appeals to recruit students that fit this description. And so the Student Board was born. The CAIU Student Board is a sub committee that directly works with the Founding Board Members. The members of the Student Board are students studying in various schools and universities. The board consists of 6 members actively participating, initiating many events and trying to reach out to a wider audience through various social media platforms. The main purpose of this board is to work as a united front of members that think in the Students’ perspective, run and support various campaigns in their respective institutions of CAIU events, and work on research. Some of the works in which the board was involved include Practitioner Series, Podcasts, Spring e-camp. Our future initiatives include Back-to-School e-camp, new episodes of podcasts and practitioner series, roadshows, poster competitions, academic writing, hands on research work, inter-school debate competition and much more. Current Initiatives Podcast. The Student Board was hoping to launch podcasts every month relating to academic integrity and the center’s several initiatives to further knowledge on this important topic. This was decided on in order to bring to awareness the issue of academic dishonesty through a platform that would be accessible to people from all over the world. So far there have been two podcasts launched. The first one an introduction to CAIU and its goals along with a brief description of the Student volunteers taking the initiative to be a part of the main Board and collaborating with the Founders of CAIU to incorporate academic integrity and honesty in schools and universities across the UAE. Our second podcast talks about a recent initiative: The 2021 Spring E-Camp conducted on the last three days of the month of March. This was deemed a huge success by both the hosts and the Camp participants. It was a Virtual Camp which consisted of several fun activities meant to educate students from different cities in the UAE about the importance of academic integrity and its enforcement. The podcast also includes the experience of two Camp participants and their feedback on it. Spring Camp. Towards the end of March, the Centre for Academic Integrity in the UAE, in collaboration with the University of Wollongong in Dubai, hosted a 3-day Ignite Integrity (I^2) Spring e-Camp, the first camp of its kind. The purpose of the spring e-camp was to enhance the student community worldwide to help develop a sense of integrity and increase awareness and interest towards academic integrity to assist school students in experiencing a smoother transition into higher education. Fifty-three students from around the world attended the camp. On the first day, the students were educated about the importance and impact of integrity on their academic careers. We held workshops on Citations and Referencing and training on Academic Integrity on the second day. On the final day, the students participated in a unique Ignite Integrity Competition where they applied the knowledge they acquired from the previous days. The campers all graduated to become Integrity Ambassadors and were presented with special e-Badges and Certificates . We received positive feedback from the students in the survey we conducted. Future Initiatives Inter School debates: schools in UAE compete, topic related to academic integrity Our first future initiative will be an event opened to schools around the UAE, as an opportunity for discussion of issues concerning academic honesty from both the educators and student’s sides. Although it will be primarily a competitive event, the main purpose of it is to encourage students to participate in an active conversation in teams, and compete based on each team’s argumentative skills, reasoning, and logic. There are also plans of an additional open discussion panel so that after the main competition is over, students and teachers can engage in civil discourse and come to their own conclusions and insights outside a competitive scene. Back to school camp. After the success of our initial Spring Camp, our next initiative is to host a similar E-Camp for Students in the month of August. The purpose of this camp will be to educate the Students on all topics related to Academic Integrity. One year anniversary: We are planning something special to celebrate our one-year anniversary, as it is an important occasion to recollect and review our past achievements, endeavours and brainstorm on what lies ahead in the future. Our Ultimate Goal Integrity is of utmost importance both in academic and professional settings. Our Centre makes its move to impact many students’ lives in relation to Academic Integrity. We aim to reach out to many and help minimize academically dishonest behaviors among students. We also aim to bring to the attention of both academic and non-academic people the importance of academic integrity and its implementation in a way that can be understood by both young and old. With the torch of academic integrity held high, we hope to create a light in many students with years to come.